Strength distribution and fracture analyses of LiNbO3 and LiTaO3 single crystals under biaxial loading. Issue 14 (November 2017) - Gruber, M.; Kraleva, I.; Supancic, P.; Bielen, J.; Kiener, D.; Bermejo, R.
Abstract: The strength distribution and fracture behaviour of miniaturized Lithium niobate (LiNbO3 ) and Lithium tantalate (LiTaO3 ) single crystals were assessed under biaxial bending. The susceptibility of these materials to environmental assisted cracking (SCCG) was studied by means of constant cross-head displacement rate experiments in air and in water. Two different sample sizes were tested and compared to assess the Weibull volume effect. Experimental results showed a significant difference in strength, LiNbO3 being weaker than LiTaO3 . No apparent SCCG and no volume effect on strength were found. A different distribution to Weibull behaviour was observed in LiNbO3 . Fractography showed differences in the fracture patterns, due to the different cutting orientation of the two investigated materials with respect to the loading plane. New cleavage planes were identified as {10.1} for LiNbO3 and {1 2 ¯ .3} for LiTaO3 . Fracture surfaces of LiNbO3 revealed surface damage, which may be responsible for the lower strength compared to LiTaO3 .